Detecting cartels - Joseph E. Harrington (The Johns Hopkins University, Department of Economics, 2005)
In reviewing the theoretical and empirical literature on collusion, this paper distills methods for detecting cartels and distinguishing collusion from competition.
Keywords: 330; Kartell; Wettbewerb; Wettbewerbsbeschränkung; Theorie